2015
DOI: 10.1136/jech-2015-206419
|View full text |Cite
|
Sign up to set email alerts
|

Evictions and suicide: a follow-up study of almost 22 000 Swedish households in the wake of the global financial crisis

Abstract: BackgroundMillions of families across the world are evicted every year. However, very little is known about the impact that eviction has on their lives. This lack of knowledge is also starting to be noticed within the suicidological literature, and prominent scholars are arguing that there is an urgent need to explore the extent to which suicides may be considered a plausible consequence of being faced with eviction.MethodThe present study's sample consists of all persons served with an application for executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 10 publications
1
50
0
Order By: Relevance
“…Firthlogit is a technique that is suited to dealing with situations in which the event of interest is rare (cf. Rojas and Stenberg 2016), which is the case here in the sense that the proportion of deaths from any cause in the data is lower than 5% (cf. King and Zeng 2001).…”
Section: Methodsmentioning
confidence: 78%
“…Firthlogit is a technique that is suited to dealing with situations in which the event of interest is rare (cf. Rojas and Stenberg 2016), which is the case here in the sense that the proportion of deaths from any cause in the data is lower than 5% (cf. King and Zeng 2001).…”
Section: Methodsmentioning
confidence: 78%
“…Evictions are one of the most common pathways to homelessness (Cusack & Montgomery, ; Desmond & Kimbro, ). In addition to homelessness, studies have shown that evictions are associated with various negative health outcomes, including long‐term stress, medical problems, substance use, depression and suicide among adults and their children (Rojas & Stenberg, ; Van Laere, De Wit, & Klazinga, ; Zivanovic et al., ). Thus, a growing number of studies have begun to conceptualise evictions as an important social and public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…One study in Catalonia found that 90% of women and 84% of men in mortgage arrears and threatened with eviction had poor mental health compared with rates of 15% and 10% in the general population (30). A Swedish study linking data on 23,000 court imposed rental evictions found that they were four times more likely to complete suicide than the general population (31).…”
Section: Original Articlementioning
confidence: 99%
“…With better awareness these professionals could then act as gatekeepers and better refer individuals to appropriate psychological and social welfare support services (44). In Sweden landlords are required to inform local government authorities if they wish to evict their tenants; this can give the local authority a chance to see what help it can provide for a tenant to avoid eviction and all the many adverse impacts that this would have (31).…”
Section: Original Articlementioning
confidence: 99%